Medicamentos e gravidez: Influência na morfologia fetal - Fernanda Sardinha de Abreu Tacon; Kelly Cristina Borges Tacon; Waldemar Naves do Amaral (UniEVANGÉLICA, 2018)
Objective: To know the factors associated with the inadequate use of drugs during the gestational period, which may help in the implementation of programs to clarify the harm to maternal-fetal health. Data source: This review searched on the databases Bireme, Scielo, PubMed, Lilacs and Site Up to Date. The selection took into account its titles and abstracts related to the subject, from 2006 to 2017, using the descriptors Use of Medications / Drug utilization, pregnancy / pregnancy and fetal development / fetal morphology. We found 75 articles, of which 33 were selected, the most recent and high theoretical content required for text construction. Data synthesis: This analysis revealed the need for greater performance of health professionals in an attempt to clarify the danger of self-medication, inadequate use of medications and the importance of healthy habits. Conclusions: therefore, new research in the area is increasingly necessary and make pregnant women aware of the dangers of medication anomalies, contributing to the improvement of public health.